PENGGUNAAN IKLAN LOWONGAN KERJA BERBAHASA INGGRIS (Suatu Kajian Isi Pada Harian Kompas) - Robert Juni Tua Sitio (Institut Agama Kristen Negeri Tarutung, 2018)
The objectives of this research are (1) to figure out some companies which use english in their announcement for job seeker in Kompas newspaper (2) to find out whether their using English announcement is suitable for Indonesian job seeker (3) to find out whether the list of identity and academic qualification of Indonesian job seekers are suitable for the qualification that companies have mentioned. The researcher uses qualitative research, by using content analysis to measure the significant of particular ideas or meanings in the text of announcement for job seekers in certain company, then collecting and interpreting the data according to the issues of socilingitics that is speech community. The results of the research are: (1) the companies need not make English announcement for job seekers since both companies and job seekers are .in indonesia (2) Their using English term in their announcement are not suitable since most of the readers and job seeker hardly understand those lists (3) the list of identity and the terms academic qualifications can not be found in Indonesia since academic qualification is still used in Indonesian not in English. Keywords: sociolinguitics, national language policy, English announcement.